Major adverse cardiovascular event (MACE) after percutaneous coronary intervention in one-year follow-up study - Farshidi, Hossein (Electron Physician, 2018)
BACKGROUND: Percutaneous coronary intervention (PCI) is the most common revascularization procedure, with over 1 million performed each year, worldwide. Over the past 20 years, the increasing experience of operators coupled with the advent of newer technologies, including coronary stents and a variety of adjuvant drug therapies, have permitted more successful procedures and decreased the morbidity associated with PCIs. OBJECTIVE: To identify the incidence, predictors, and clinical implications of Major Adverse Cardiovascular Events (MACE) after PCIs. METHODS: This descriptive cross-sectional study was done in Bandar Abbas in Iran in 2015. All patients which treated with PCI in Shahid Mohammadi Hospital during a one-year period were employed. A total of 192 patients were included. At one-year follow-up in this study, incidence and predictors of MACE were evaluated in a prospective study. The data were analyzed by SPSS 19.0 and descriptive tests included frequency and percentage and mean and standard deviation. Also, Chi-square test was used for data analysis. A p value <0.05 was determined as significant. RESULT: Of the 192 patients, 126 (65.6%) were men and 66 patients were female. Stent had been implemented in 93.8% of patients. Sixty two percent of patients were treated with only one stent, two stents were deployed in 29.7% of patients and 3.6% of patients were treated with three or more stents. Of these patients, 46.9% were treated with Drug Eluted Stent (DES) and 40.1% were treated with Bare Metal Stent (BMS). Both types of stents were used in 8.3% of patients. Also, 4.7% of the patients were treated with balloon angioplasty (POBA). Angioplasty success rate was 95.3% and procedural success rate defined as achieving TIMI III flow with residual coronary stenosis under 30%. No in-hospital mortality or emergency CABG was reported. Re-admission in first year after PCI was required in 34 (17.7%) patients of which, 20 of them (10.4%) needed target vessel revascularization (TVR). Readmission was significantly higher (p=0.034) in the group with BMS compared to those who had DES. MI occurred in 8 patients. CONCLUSION: Our study showed the superiority of DES in comparison with BMS in decreasing readmission and less TVR, but no effect on long term mortality. We recommend more studies in this setting because patients in special groups may benefit more from DES or BMS.